Experimental comparison of Superpave and Marshall methods - Namli, Remzi; Kuloglu, Necati (Turkish Chamber Civil Engineers, 2007)
In this study, asphalt concrete specimens were prepared according to The Superpave and Marshall mix design methods, were compared according to their design specifications. Gyratory compactor developed by The Firat University Sciencific Research Project Unit (FUBAP) was used. The specimens prepared according to the stability, specific gravity, percent air void, voids in mineral aggregate and flow. In this comparison, the advantages and disadvantages of both methods were evaluated. Design binder content of Superpave specimens were determined to be less than that of Marshall specimens.
Superpave ve Marshall yöntemlerinin deneysel karşilaş tirilmasi